Odpowiedzi

2009-12-22T14:33:05+01:00
X³-4x²-x+4=0
x(x^2-1)-4(x^2-1)=0
(x^2-1)(x-4)=0
x^2-1=0 lub x-4=0
x^2=1 lub x=4
x=1 lub x=-1 lub x=4




x⁴+x³-12x²=0
x^2(x^2+x-12)=0
x^2=0 lub x^2+x-12=0
x=0 lub delta= b^2-4ac=1^2-4*1*(-12)=49
pierw z delty=7
x1= -4 lub x2=3
x=0 lub x=-4 lub x=3
4 1 4
2009-12-22T14:34:55+01:00
A) x³-4x²-x+4=0
x(x²-1)-4(x²-1)=0
(x-4)(x²-1)=0
x=4,lub x=1, lub x=-1

b)x⁴-3x³-3x²-x=0
x³(x-1)-3x²(x-1)=0
(x³-3x²)(x-1)=0
x²(x-3)(x-1)
x=0,lub x=3, lub x=1

c) x⁴+x³-12x²=0
x²(x²+x-12)=0
delta=1+48=49
pierwiastek z delta=7
x1=-1-7/2=-4
x2=-1+7/2=3
x=0, lub x=-4, lub x=3.
4 5 4
Najlepsza Odpowiedź!
2009-12-22T14:35:24+01:00
X³ - 4x² - x + 4 = 0
x²(x-4)- 1(x-4)=0
(x²-1) (x-4) = 0
x²-1 = 0 ∨ x-4=0
x=1 ∨ -1 x=4


x⁴-3x³-3x²-x=0
x²(x²-3) - x (3x+1= 0
(x²-x) (x²-3) (3x+1) = 0
x²-x = 0 ∨ x²-3 = 0 ∨ 3x+1 = 0
x²=x //x x²=3 x = - 1/3
x=1 x=√3 ∨ -√3


x⁴+x³- 12x² =0
x²(x²+x-12)=0
x²=0 x=0
Δ= b²-4ac= 1- (48) = 49 √Δ=7
x₁= (-b-7)/2a= -8/2= -4
x₂= (-b+7)/2a= 6/2=3
2 3 2